Surface plasmon resonance‐induced Ag‐BaTiO3 composites for catalytic performance. Issue 9 (24th May 2021) - He, Zemin; Yu, Ping; Wang, Haiyang; Gao, Jianjing; Zhao, Yang; Zhang, Haiquan; Zhao, Yuzhen; Miao, Zongcheng
Abstract: Ferroelectric BaTiO3 was combined with Ag nanoparticles for piezocatalytic and photocatalytic viewpoints. Microstructural characterization (X‐ray diffraction and electron microscopy images) revealed that the Ag was successfully bounded with BaTiO3 . X‐ray photoelectron spectrum also confirmed the presence of Ag. Further, its performance was examined for dye degradation under visible light (for photocatalysis) and ultrasonication (for piezocatalysis). In both the catalysis processes, there was a significant improvement in Ag‐loaded BaTiO3 sample‐based catalytic reactions. Catalytic performance was evaluated for multiple cycles and was found consistent. Scavenger tests were also performed to understand catalytic reactions.